Ion beam synthesis of embedded III‐As nanocrystals in silicon substrate. Issue 1 (29th October 2014) - Khelifi, Rim; Frégnaux, Mathieu; Le Gall, Yann; Muller, Dominique; Schmerber, Guy; Mathiot, Daniel
Abstract Our goal is to use the versatility of ion beam synthesis to grow nanocrystals of InxGa1‐xAs alloys embedded in a silicon substrate. We study, first, the annealing conditions necessary to grow well defined InAs and GaAs binary nanocrystals. High dose of As, Ga and In is implanted, respectively, at 130, 130 and 180 keV to have overlapping as‐implanted profiles. The nanocrystals growth is then achieved by rapid thermal annealing at various temperatures between 650 and 800 °C for 1 min under an argon gas flow. Rutherford backscattering spectroscopy profiles show that no significant impurity out‐diffusion occurs below 800 °C for both systems. In and As thermal redistributions lead to superposed profiles. Raman spectroscopy measurements prove that InAs nanocrystals are formed above 650 °C, while 800 °C annealing is necessary to obtain GaAs nanocrystals and show that these thermal budgets are enough to fully recrystallize the implanted layer. Grazing incidence X‐ray diffraction patterns exhibit clearly InAs and GaAs related peaks. These results prove that GaAs and InAs nanocrystals can be grown in a common temperature range (700‐800 °C), opening the route to the growth of ternary InxGa1‐xAs alloys in the same conditions. (© 2015 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)